Analysis of the impact of social interaction on learning interest at daarul qur'an islamic boarding school - Feby Miftah Azmi Khairo; Wahid Abdul Kudus (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
This study aims to analyze the pattern of social interaction on the learning interests of students at the Daarul Qur'an Islamic Boarding School. This study uses a qualitative descriptive method with data collection techniques through, direct observation and in-depth interviews with students, teachers, and caregivers The results of this research show that the quality of social interaction is a factor that greatly affects learning interest. The pattern of teacher-student interaction (superordination-subordination) becomes effective and increases motivation when teachers adopt interactive, dialogical, and innovative models (such as PBL and PjBL), Based on the results of the study, it is concluded that it is necessary to evaluate the schedule of activities that must be carried out by teachers in using interactive techniques.